A study on palmoplantar keratodermas in childhood in a district hospital - Neerja Puri (Wolters Kluwer Medknow Publications, 2017)
Introduction: Palmoplantar keratodermas (PPKs) are a group of disorders in which there is marked thickening of the skin of palms and soles. The keratodermas can be diffuse, focal, or punctuate type. Aims: The aim of this study was to study various types of PPKs, both hereditary and acquired in children up to 17 years of age. Methods: A randomized controlled prospective study of twenty patients of PPK was taken up for the study. A detailed history, general physical examination, cutaneous examination with special examination of the oral mucosa, teeth, and nails along with routine investigations were done in all the patients. Results: Most common causes of PPK were secondary to psoriasis and ichthyosis (25% each), followed by 15% cases secondary to pityriasis rubra pilaris. PPK due to pachyonychia congenita was seen in 5% patients and secondary to erythrokeratodermia variabilis in 5% patients. Monogenic PPKs including Vorners syndrome and Unna-Thost PPK were seen in 5% patients each and focal PPK seen in 15% patients. Conclusion: It is important to note the age of onset of the keratodermas, severity of disease process, and the histopathological findings before reaching a diagnosis of PPKs.